Exploring the Therapeutic Potential of Phytoconstituents for Addressing Neurodegenerative Disorders - Kamboj, Sweta; Sharma, Prerna; Kamboj, Rohit; Kamboj, Shikha; Hariom; Girija; Guarve, Kumar; Dutt, Rohit; Verma, Inderjeet; Dua, Kamal; Rani, Nidhi (Central Nervous System Agents in Medicinal Chemistry, 2024)
Neurodegenerative disorder is a serious condition that is caused by abnormal or no neurological function. Neurodegenerative disease is a major growing cause of mortality and morbidity worldwide, especially in the elderly. After World War 133;¡, eugenics term was exterminated from medicines. Neurodegenerative disease is a genetically inherited disease. Lifestyle changes, environmental factors, and genetic modification, together or alone, are involved in the occurrence of this disorder. The major examples of neurodegenerative disorders are Alzheimer's and Parkinson’s disease, in which apoptosis and necrosis are the two major death pathways for neurons. It has been determined from various studies that the etiology of the neurodegenerative disease involves the role of oxidative stress and anti-oxidant defence system, which are prime factors associated with the activation of signal transduction pathway that is responsible for the formation of synuclein in the brain and manifestation of toxic reactions in the form of functional abnormality, which ultimately leads to the dysfunction of neuronal pathway or cell. There has not been much success in the discovery of effective therapy to treat neurodegenerative diseases because the main cause of abnormal functioning or death of neurons is not well known. However, the use of natural products that are derived from plants has effective therapeutic potential against neurodegenerative disease. The natural compounds with medicinal properties to prevent neurological dysfunction are curcumin, wolfberry, ginseng, and Withania somnifera. The selection and use of natural compounds are based on their strong anti-inflammatory and anti-oxidant properties against neurodegenerative disease. Herbal products have active constituents that play an important role in the prevention of communication errors between neurons and neurotransmitters and their respective receptors in the brain, which influence their function. Considering this, natural products have great potential against neurodegenerative diseases. This article reviews the natural compounds used to treat neurodegenerative diseases and their mechanisms of action.
Keywords: neurological dysfunction